2021
DOI: 10.3390/biomedicines9121832
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen Deficiency Significantly Reduces Vascular Wall Disease in a Murine Model of Type IIa Hypercholesterolemia

Abstract: The fibrinolytic system has been implicated in the genesis and progression of atherosclerosis. It has been reported that a plasminogen (Pg) deficiency (Plg−/−) exacerbates the progression of atherosclerosis in Apoe−/− mice. However, the manner in which Plg functions in a low-density lipoprotein-cholesterol (LDL-C)-driven model has not been evaluated. To characterize the effect of Pg in an LDL-C-driven model, mice with a triple deficiency of the LDL-receptor (LDLr), along with the active component (apobec1) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Liver macrophage foaming is one of the key factors in understanding the pathophysiology of NASH, and we were able to assess foaming using L −/− / A −/− mice. In L −/− /A −/− /Plg −/− mice, macrophage foaming in NASH was suppressed, which is consistent with atherosclerosis [14–16] (Figure 3). The above was also observed upon administration of TXA, which inhibits lysine‐mediated binding of Plg (Figure 3).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Liver macrophage foaming is one of the key factors in understanding the pathophysiology of NASH, and we were able to assess foaming using L −/− / A −/− mice. In L −/− /A −/− /Plg −/− mice, macrophage foaming in NASH was suppressed, which is consistent with atherosclerosis [14–16] (Figure 3). The above was also observed upon administration of TXA, which inhibits lysine‐mediated binding of Plg (Figure 3).…”
Section: Discussionsupporting
confidence: 60%
“…Plasminogen-deficient mice (Plg À/À ) and L À/À /A À/À mice, previously described [20,[22][23][24][25], were backcrossed with the C57Bl/6J strain (Jackson Laboratory, Bar Harbor, ME, USA) for at least seven generations before cross-breeding. Triple heterozygous (L +/À /A +/À / Plg +/À ) mice were crossed with L À/À /A À/À mice to produce L À/À /A À/À /Plg +/À mice [16]. The control mice were injected with saline at 1 to 3 days of age and only male mice were fed the standard diet (5L37; PMI Nutrition International, St. Louis, MO, USA) from 28 days of age.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently revealed that the L -/-/A -/mice develop atherosclerotic plaques with several key features of LDL-driven atherosclerosis reported in the patients with type IIa dyslipidemia [69]. We have also provided evidence that this mouse model is useful for studying the pathophysiology of several diseases, including fibrinogen deficiency, plasminogen deficiency, and aortic aneurysms, in relation to LDLcholesterol-driven atherosclerosis [68,70,72].…”
Section: Limitations Of Current Mouse Models For the Study Of Atheros...mentioning
confidence: 90%
“…The frequencies of each type in Japanese male population were reported as 0.1%, 32.2%, 20.9%, 0.3%, 44.6%, and 1.9%, respectively; while those in Japanese female population were reported as 0.3%, 53.3%, 22.8%, 0.7%, 21.5%, and 1.4%, respectively [67]. Although mice deficient in apoE or Ldlr have been extensively used, mice that are fed a normal chow diet do not mimic type IIa dyslipidemia, which is one of the most common types in human dyslipidemia [68][69][70].…”
Section: Limitations Of Current Mouse Models For the Study Of Atheros...mentioning
confidence: 99%